Pengaruh Fraksi Massa Terhadap Kekuatan Bending Dan Daya Serap Air Komposit Partikel Kayu Bayur Dengan Matriks Epoxy - Alvarez, Averio; Kencanawati, C.I.P.K; Negara, D.N.K Putra (Teknik Desain Mekanika, 2025)
Abstract One effort to make composite materials more efficient is to find the latest innovations, which are cheaper, more useful, and cause less pollution. One natural material that can be used as a composite material is bayur wood particles with an epoxy resin matrix. This research aims to determine the effect of variations in the mass fraction of bayur wood particles and epoxy resin on bending strength and water absorption strength. The tests carried out on the specimens were the bending test (ASTM D790-03 and the water absorption test (D570-98). The bending test results showed the highest bending stress at a mass fraction of 5%: 95% with an average value of 133.47 MPa and a stress value of the lowest bending was at a mass fraction of 15%: 85% with an average value of 83.94 MPa. The highest bending strain value was at a mass fraction of 5%: 95% with an average value of 0.0185 mm and the lowest bending strain value was at a mass fraction of 15% : 85% with an average value of 0.0139 mm. The highest bending elastic modulus value is at a mass fraction of 5% : 95% with an average value of 7928.72 MPa and the lowest elastic modulus value is at a mass fraction of 15% : 95% with an average value. -average 6817.99 MPa. In the water absorption test, the highest value was 1.19% at a mass fraction of 15%: 85% and the lowest water absorption value was at a mass fraction of 5%: 95% with an average value of 0.65%. Keyword : bayur wood particles, particle board, bending test, bending test, water absorption test, epoxy